Parental Influences on Children's Self-Regulation of Energy Intake: Insights from Developmental Literature on Emotion Regulation - Leslie A. Frankel; Sheryl O. Hughes; Teresia M. O'Connor; Thomas G. Power; Jennifer O. Fisher; Nancy L. Hazen (Hindawi Limited, 2012)
The following article examines the role of parents in the development of children's self-regulation of energy intake. Various paths of parental influence are offered based on the literature on parental influences on children's emotion self-regulation. The parental paths include modeling, responses to children's behavior, assistance in helping children self-regulate, and motivating children through rewards and punishments. Additionally, sources of variation in parental influences on regulation are examined, including parenting style, child temperament, and child-parent attachment security. Parallels in the nature of parents' role in socializing children's regulation of emotions and energy intake are examined. Implications for future research are discussed.